Enhanced variant neutralization through glycan masking of SARS-CoV-2 XBB1.5 RBD - Joey Olivier; Charlotte George; Chloe Qingzhou Huang; Sneha B. Sujit; Paul Tonks; Diego Cantoni; Joe Grove; Laura O’Reilly; Johannes Geiger; Christian Dohmen; Verena Mummert; Anne Rosalind Samuel; et al. (Emerging Microbes and Infections)
SARS-CoV-2 continues to evolve antigenically under the immune pressure exerted by both natural infection and vaccination. As new variants emerge, we face the recurring challenge of updating vaccines at significant financial cost to maintain their efficacy. To address this, novel strategies are needed to enhance the breadth of protection offered by vaccines or, at a minimum, extend their effectiveness over time. One such strategy is antigen modification. In this study, we introduce a glycosylation site into a binding but non-neutralizing epitope within the SARS-CoV-2 XBB.1.5 receptor binding domain (RBD) to redirect the immune response towards more potent neutralizing epitopes. Immunization of mice with this modified antigen via the mRNA vaccine platform resulted in a dramatic increase in neutralizing antibodies compared to the wild-type XBB.1.5 RBD, showing superior protection against a range of SARS-CoV-2 Omicron variants, from BA.2 to JN.1. Our findings reinforce the power of the glycan masking approach, which in combination with the now well-established mRNA vaccine platform can contribute to broader and better vaccines.